Strategi Komunikasi Mengelola Persepsi Publik dalam Rebranding ACE Hardware ke AZKO - Anandianskha, Sawaviyya (LUGAS Jurnal Komunikasi, 2025)
Rebranding is a crucial strategy for companies to maintain relevance andcompetitiveness in an ever-evolving market. PT Aspirasi Hidup Indonesiaunderwent a significant rebranding effort by changing its name and brandidentity from ACE Hardware to AZKO. The primary objective was toidentify the key messages crafted within the rebranding communicationstrategy, including the elements used to build AZKO's new brand image. Aqualitative approach with a descriptive method was applied through directobservation, document analysis, and literature review. Findings revealthat AZKO's rebranding communication focused on three core elements:innovation, inspiration, and local relevance. The message "Your HomeLife Improvement Partner" was consistently conveyed through visualelements such as a new logo featuring an open circle, minimalist stagedesigns at the Bundaran HI launch event, and digital media, including thelargest videotron in Jakarta at Mall Taman Anggrek. The launch event,attended by thousands, included a symbolic moment with spotlightprojections of "ACE berubah jadi AZKO" (ACE changes to AZKO). Thecommunication strategy also leveraged influencer collaborations toexpand its reach. In conclusion, AZKO's rebranding communicationstrategy successfully established a new, relevant identity positivelyreceived by the audience. The consistency of messaging, the strength ofvisual elements, and a focus on local relevance were key factors in itssuccess. These findings contribute to the literature on rebrandingcommunication strategies and offer practical guidance for othercompanies undergoing similar brand transitions